Numerical Simulation of Slope Excavation and Stability Under Earthquakes in Cataclastic Loose Rock Mass of Hydropower Station on Lancang River - Wenjing Liu; Hui Deng; Shuo Tian (Applied Sciences)
This study investigates the excavation of the cataclastic loose rock slope at the mixing plant on the right bank of the BDa Hydropower Station, which is situated in the upper reaches of Lancang River. The dominant structural plane of the cataclastic loose rock mass was obtained using unmanned aerial vehicle tilt photography and 3D point cloud technology. The actual 3D numerical model of the study area was developed using the 3DEC discrete element numerical simulation software. The excavation response characteristics and overall stability of the cataclastic loose rock slope were analyzed. The support effect was evaluated considering the preliminary shaft micropile and Macintosh reinforced mat as slope support measures, and the stability was assessed by applying seismic waves. The results showed the main deformation and failure area after slope cleaning excavation at the junction of the cataclastic loose rock mass and Qedl deposits in the shallow surface of the excavation face. Moreover, the maximum total displacement could reach 18.3 cm. Subsequently, the overall displacement of the slope was significantly reduced, and the maximum total displacement decreased to 2.78 cm. The support effect was significant. Under an earthquake load, the slope with support exhibited considerable displacement in the shallow surface of the excavation slope, with collapse deformation primarily occurring through shear failure.